Precision Livestock Farming IT Support Model for the Poultry Industry - Ņikitenko, Agris; Bāliņa, Signe; Dubrovskis, Andrejs; Andersone, Ilze; Birzniece, Ilze (Complex Systems Informatics and Modeling Quarterly, 2022)
The presented work proposes a practical approach to bird weight data processing and augmentation to enable production outcome forecast model training, which contributes to higher productivity. We suggest using the parametrized model, where parameter values are found through genetic optimization and thus are closely corresponding to broiler body weight factual measurements. The proposed approach is implemented as a stand-alone software system, exposing the models through containerized web services enabling different use scenarios.